The Crisis of Statelessness and Refugee Rights in International Law - Seema Gul; Mehmoona Allauddin; Fayaz Ahmad (Indus Journal of Social Sciences, 2025)
The global crises of statelessness and forced displacement continue to challenge the foundational tenets of international law and human rights protection. Stateless individuals those not recognized as nationals by any state and refugees frequently fall through legal and institutional gaps, rendering them among the most vulnerable populations worldwide. This study critically examines the international legal frameworks governing statelessness and refugee rights, primarily the 1951 Refugee Convention, and the 1954 and 1961 Statelessness Conventions. Using doctrinal legal analysis and case studies such as the Rohingya and climate-displaced communities, the research identifies key shortcomings in state compliance, the inadequacy of enforcement mechanisms, and the exclusionary impact of sovereignty over nationality laws. It also explores emerging normative developments, including expanded refugee definitions and advocacy efforts like the UNHCR’s. The findings suggest that while a legal foundation exists, significant reforms such as enhancing accountability, harmonizing nationality laws, and accommodating climate-induced displacement are urgently needed. The study concludes by proposing a recalibration of international legal obligations to ensure no person is left without nationality, rights, or legal protection in a rapidly evolving global context. Statelessness and the displacement of refugees present a formidable challenge to international law, threatening the protection of fundamental human rights. Despite significant legal frameworks such as the 1951 Refugee Convention and the 1954 and 1961 Statelessness Conventions, millions remain without legal nationality or adequate protection. This article critically examines the international legal regime governing stateless persons and refugees, identifies systemic gaps and enforcement shortcomings, and proposes reforms to ensure better alignment with human rights standards in the face of contemporary crises such as conflict, climate change, and exclusionary citizenship laws.